Is routine histopathology of tonsil specimen necessary? - Agida S Adoga; Danle N Ma`an; Samuel I Nuhu (Wolters Kluwer Medknow Publications, 2011)
Background: Tonsillar diseases are common in paediatric and adult otolaryngological practice. These diseases require tonsillectomy. Specimens are subjected to histopathology routinely in my institution for fear of infections and tumour without consideration for risk factors. The financial burden is on the patients and waste of histopathologist's man hour because other specimens are left un-attended. This study aims to find out the necessity of routine histopathology of tonsil specimens. Materials and Methods : A 2 year retrospective review of the histopathological results of two (paediatric and adult) groups of 61 patients managed for tonsillar diseases at the ENT UNIT of Jos University Teaching Hospital from July 2005 to June, 2007. Data extracted included biodata, clinical features and histopathological diagnosis. Result : The 61 patients comprise 35 children and 26 adults. The youngest and oldest paediatric patients were 1 year and 3 months and 16 years respectively, a range of 1 year 3 months to 16 years. The youngest and oldest adults were 17 and 50 years with a range of 17-50 years. Groups mean ages were 5.1 and 28.5 years. The gender ratios were 1:2.7 and 1:1.9 respectively. One adult was HIV positive. The histopathological diagnosis were chronic nonspecific tonsillitis in 10(16.6%), follicular tonsillitis in 23(38.3%), chronic suppurative tonsillitis in 10(16.6%), lymphoid hyperplasia in 18(30.0%) and lymphoma in 1(1.0%) respectively. Conclusion : Histopathologic request for tonsillectomy specimens should be based on certain risk factors with consideration of the cost to patients and to spare the histopathologist's man hour.